2023
DOI: 10.1002/hed.27299
|View full text |Cite
|
Sign up to set email alerts
|

The role of radiomics in tongue cancer: A new tool for prognosis prediction

Abstract: Background: Radiomics represents an emerging field of precision-medicine. Its application in head and neck is still at the beginning. Methods: Retrospective study about magnetic resonance imaging (MRI) based radiomics in oral tongue squamous cell carcinoma (OTSCC) surgically treated (2010-2019; 79 patients). All preoperative MRIs include different sequences (T1, T2, DWI, ADC). Tumor volume was manually segmented and exported to radiomic-software, to perform feature extraction. Statistically significant

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…7 The machine learning model with radiomics features yielded better results for the prediction of cervical lymph node metastasis compared with the deep learning model using ultrasonographic images or measurements of the longest diameter and thickness in previous reports. Most studies using radiomics analysis have used CT 14 or MRI, 12 and few have used ultrasonographic images, mainly been due to uncertainty regarding the obtained images. Recently, however, some radiomics studies using ultrasonographic images have been reported, including several studies involving comprehensive liver tumor evaluations, including differential diagnosis and clinical prognosis, 27 and prediction of lymph node metastasis in breast cancer 28 and in the head and neck region.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…7 The machine learning model with radiomics features yielded better results for the prediction of cervical lymph node metastasis compared with the deep learning model using ultrasonographic images or measurements of the longest diameter and thickness in previous reports. Most studies using radiomics analysis have used CT 14 or MRI, 12 and few have used ultrasonographic images, mainly been due to uncertainty regarding the obtained images. Recently, however, some radiomics studies using ultrasonographic images have been reported, including several studies involving comprehensive liver tumor evaluations, including differential diagnosis and clinical prognosis, 27 and prediction of lymph node metastasis in breast cancer 28 and in the head and neck region.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies using radiomics analysis have used CT 14 or MRI, 12 and few have used ultrasonographic images, mainly been due to uncertainty regarding the obtained images. Recently, however, some radiomics studies using ultrasonographic images have been reported, including several studies involving comprehensive liver tumor evaluations, including differential diagnosis and clinical prognosis, 27 and prediction of lymph node metastasis in breast cancer 28 and in the head and neck region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, due to the development of ML algorithms coupled with more accessible digital data, more and more researchers have begun to focus on predicting molecular biomarkers, therapeutic responses, and survival prognostic factors in patients with head and neck (HN) carcinomas by extracting radiomics information features (e.g., shape description, intensity, or texture characteristics) from different imaging patterns (e.g., CT, MRI, PET, ultrasound images) [11]; in Mossinelli's [12] retrospective study on 79 patients with oral tongue squamous cell carcinoma (OTSCC) MRI-based radiomics represents a promising noninvasive method of precision medicine, improving prognosis prediction before surgery.…”
Section: Introductionmentioning
confidence: 99%